Pharmacist Recommendations for Non-Infectious Diarrhea Self-Medication: A Study in Padang, Indonesia - Hansen Nasif; Dwisari Dillasamola; Wira Sanjaya; Dian Ayu Juwita (Journal of Public Health and Pharmacy)
Introduction: Diarrhea is a condition where a person defecates with a soft or liquid stool consistency or even just water which can be accompanied by blood or foam with a frequency that is more frequent than usual in a day. Self-medication is an action taken by someone to treat themselves by recognizing the symptoms and illnesses felt, usually minor illnesses, then choosing drugs according to their wishes without going through a doctor's prescription.